Does Learning English Contribute to Ensuring Patient Safety? Egyptian Cardiac Nurses Perceptions - Amr Selim Wannas (Mitra Palupi, 2023)
Background: The effect of English is indisputable in the profession of nursing, where English is increasingly becoming the medium of instruction and communication. Therefore, the principal goal of the study was to examine the perceptions of Egyptian nurses in reference to the English language effect on patient safety. Purpose: The study was implemented in a cardiothoracic Centre that provides free-of-charge care for patients with heart diseases. Design and methods: In this pursuit, a mixed-method approach was employed as two data collection instruments were constructed and utilized following the review of literature and based on the patient international safety goals recommended by the Joint Commission International (JCI). The first instrument is a 39-item questionnaire and the second is a semi-structured interview. The number of nurses participated in the study was (n=94); 86 nurses participated in the questionnaire whereas eight expert nurses were recruited for the semi-structured interview. Results: The results revealed that the English language is an essential element in the process of ensuring patient safety for Egyptian nurses and its effect is revealed through the international safety goals. Based on the study, nurses are advised to be proficient in using the English language so as to provide the best possible care for cardiac patients.